Letter (copy) - Citrine, Walter, 1887-1983
011-0063-001 WMC/FEM/FP/420 Secretary's. 19th July, 1937. Senor T. de Lizaso, London Delegation, Spanish Embassy, 24, Belgrave Square, London, S. W. 1. Dear Senor Lizaso, I have only just had an opportunity of reading your letters of the 9th, 10th, 12th and 13th July. I thank you very much for sending me the information contained in these letters. The delay in replying was due to the fact that I have been out of the country, and have only just returned. As the letters were sent to my private address they were not acknowledged. Otherwise they would have been dealt with at the office in my absence. Yours sincerely, General Secretary. 292/946/11/63